Differences in Giving of Mc Kenzie Exercise and Core Stability Exercise toward Functional Activity of Patients with Lower Back Pain in GrandMed Hospital Lubuk Pakam - Tati Murni Karokaro; Melisa Queen Hutabarat (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2018)
In fulfillment of these needs sometimes human forget to maintain their health, good attitude so that the position in work is not ergonomic which can lead to problems when carrying out activities. Lower back pain is a clinical symptom that is characterized by pain or a discomfort feeling in lower back area. In the United States, the incidence of lower back pain region in the past one year is 15% -20%. This study aims to see whether there were differences in giving of Mc Kenzie and Core Stability Exercise toward Functional Activity of Patients with Lower Back Pain. This study is quasi experiment with a sample of patients with lower back pain, with purposive sampling technique. The results obtained are p-value ? <(0,000 <0,05), it means that there is a difference in giving of Mc Kenzie Exercise toward the increase of Functional Activity of Patients with Lower Back Pain, that uses body movements that is directed to extension, to provide strengthening and reflecting on the extensor and flexor muscles of the lumbar joint, while the Core Stability Exercise has the ability to regulate the position and movement in the central region of the body, and it can be concluded that there is differences in Giving of Mc Kenzie Exercise toward the increase of Functional Activity of Patients with Lower Back Pain. It is recommended for patients who experience lower back pain so that keep always repeat the exercises that suggested by physiotherapist, for further research so that choose more samples.